Validity and reliability of the movement behaviour questionnaire child in Chinese preschoolers - Song, Huiqi; Lu, Nike; Wang, Jingjing; Lau, Patrick W. C.; Zhou, Peng (Frontiers in Pediatrics, 2025)
BackgroundThe Movement Behaviour Questionnaire Child (MBQ-C) was developed to measure physical activity, screen time, and sleep in preschool children, but the Chinese version lacked validation.MethodsThis cross-sectional study aimed to assess the validity and reliability of the open-ended version of the MBQ-C among Chinese preschoolers. Data were collected from 892 parents of children aged 0–5 years across 10 provinces via an online questionnaire. The MBQ-C includes items on physical activity, screen time, and sleep, and was validated against device-measured physical activity using accelerometers.ResultsInternal consistency was high, with Cronbach's alpha values ranging from 0.80 to 0.88 for different sections. Test-retest reliability showed moderate intraclass correlation coefficients (ICCs) between 0.52 and 0.72. Confirmatory factor analysis indicated good construct validity (CFI = 0.95). Moderate significant correlations were found between MBQ-C reported physical activity and device-measured moderate-to-vigorous physical activity (R = 0.35, p < 0.001).ConclusionThe open-ended version of the MBQ-C demonstrates good validity and reliability in assessing movement behaviours among Chinese preschoolers. This tool is effective for proxy-reported measurements and can contribute to understanding and promoting healthy movement behaviours in early childhood.